1993
DOI: 10.1007/bf00144577
|View full text |Cite
|
Sign up to set email alerts
|

Transport and metabolism of indole-3-butyric acid in cuttings of Leucadendron discolor

Abstract: indole-3-butyric acid (IBA) greatly enhanced the rooting of an early-flowering variety of protea, Leucadendron discolor, but had very little effect on a late-flowering variety . IBA transport and metabolism were studied in both varieties after incubating the cuttings in 'H-IBA . More of the radio-label was transported to the leaves of the easy-to-root variety than the difficult-to-root (35-45% and 10%, respectively) . IBA was metabolized rapidly by the cuttings of both varieties and after 24 h most of the labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The formation of the large amount of ester-linked IBA is consistent with what was found previously, and the major conjugate is most likely IBA-Glc (Epstein and Ackerman, 1993;Baraldi et al, 1995). On the other hand, the total amount of free and conjugated [ Tognetti et al (2010) found that the gene encoding the IBA-Glc-conjugating enzyme (UGT74E2) was rapidly and strongly induced by oxidative stress and the level of IBA-Glc was dramatically increased under stress conditions, it is possible that the IBA-Glc-conjugating activity was significantly induced at the cut surface of the hypocotyl and that the formation of IBA-Glc conjugates led to more IBA taken up into the plant tissue.…”
Section: Discussionsupporting
confidence: 90%
“…The formation of the large amount of ester-linked IBA is consistent with what was found previously, and the major conjugate is most likely IBA-Glc (Epstein and Ackerman, 1993;Baraldi et al, 1995). On the other hand, the total amount of free and conjugated [ Tognetti et al (2010) found that the gene encoding the IBA-Glc-conjugating enzyme (UGT74E2) was rapidly and strongly induced by oxidative stress and the level of IBA-Glc was dramatically increased under stress conditions, it is possible that the IBA-Glc-conjugating activity was significantly induced at the cut surface of the hypocotyl and that the formation of IBA-Glc conjugates led to more IBA taken up into the plant tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Additional studies have examined the distribution of radiolabeled IBA after application of a rooting solution to the base of explants. In most cases, however, these studies were not designed to distinguish between movement of auxin in the plant's vascular system and polar auxin transport (for example, see Epstein and Lavee, 1984;Wiesman et al, 1988;van der Krieken et al, 1992;Epstein and Ackerman, 1993). In one notable exception, IBA polar transport was examined in excised citrus leaf midribs and found to be twice as high in the basipetal direction as in the acropetal direction (Epstein and Sagee, 1992).…”
mentioning
confidence: 97%
“…This theory is supported by reports on increased levels of free auxin in the bases of cuttings prior to rooting (Brunner 1978, Moncousin et ai. 1989, Liu and Reid 1992, Epstein and Ackerman 1993 used the conjugate inhibitor 2,6-dihydroxyacetophenone (DHAP, Lee and Starratt 1986) in order to increase the level of free auxin in cuttings of the difficult-to-root olive cv, Uovo di Piccone. Significantly more cuttings rooted following treatment with 2 mM DHAP and 0.8% IBA than with 0.8% IBA alone (30% vs 15%, respectively).…”
Section: Iba Conjugatesmentioning
confidence: 99%
“…However, when they used stem segments from cuttings which were pretreated with 10 mg ml ' of IBA for 24 h they noticed an increase in the translocation of IAA. In an experiment with L, i/(.yco/or (Epstein and Ackerman 1993), cuttings of easyand difficult-to-root cultivars were incubated with labeled IBA. The major difference in the transport between the two cultivars was that in the difficult-to-root cultivar the label in the leaves was almost a constant 10% of the total uptake, while in the easy-to-root leaves the value increased after 2 weeks to 30% and after 3 weeks to 45% , with a final level of 357o after 4 weeks (the same as in the shoot).…”
Section: Uptake and Transport Of Ibamentioning
confidence: 99%